Evaluasi Implementasi Jaminan Persalinan (Jampersal) di Indonesia - Mukhlisa, Mazda Novi; Estetika, Rosa (Jurnal Ekonomi Kesehatan Indonesia, 2020)
Jampersal as a transfer fund from central to district government is provided to support maternal and child health services aiming to increase access to health services for pregnant women, childbirth and postpartum mothers, also newborns to competent health facilities. This analysis aimed to evaluate the use of Jampersal in increasing institutional delivery using quantitative and qualitative approaches. For the quantitative approach, this analysis used Riskesdas 2018 and routine data from the Ministry of Health. The data was analyzed using benefit incidence analysis (BIA) and linear regression. The quantitative approach was conducted at two levels, the individual level (80,459 pregnant women) and the district level (407 districts), whereas the qualitative approach was conducted in eight districts to enrich quantitative results. Information was managed using content analysis. Results indicated that Jampersal held 3.75% of the total funding of child delivery. Jampersal spending tends to increase every year and is utilized mostly for services. BIA showed that Jampersal is widely used by mothers whose heads of households are at the primary education level. Regression analysis showed that every rupiah spent in Jampersal increases institutional delivery, although it is not statistically significant (coefficient 0.000726; robust SE 0.00370; p-value> 0.1).